2018
DOI: 10.18535/ijsrm/v6i3.fe01
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Beneficiary Satisfaction with Community Based Solid Waste Management Service. A case of Okoa Maisha Project in Mnarani Village, Kilifi County, Kenya

Abstract: Solid Waste Management Service (SWMS) is an important public good, although most local governments in developing countries have failed to effectively provide it to their populace. Ineffective SWMS has serious environmental and public health ramifications. Consequently, other players such as NonGovernmental Organizations (NGOs), private companies and Community Based Organizations (CBOs) have to be involved in the delivery of SWMS. This study assessed the level of beneficiary for households" satisfaction with SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This was attributable by the fact that the participating households were obtaining financial benefits (mean=3.61). A study by Hassan et al (2018) also reported similar findings of high participation at the implementation stage of CDD projects.…”
Section: Levels Of Participation In the Cdd Subprojectssupporting
confidence: 61%
See 1 more Smart Citation
“…This was attributable by the fact that the participating households were obtaining financial benefits (mean=3.61). A study by Hassan et al (2018) also reported similar findings of high participation at the implementation stage of CDD projects.…”
Section: Levels Of Participation In the Cdd Subprojectssupporting
confidence: 61%
“…A possible reason was due to the moderate incorporation of CDD elements in CDD subprojects. The overall level of participation reported here is lower than in other African countries (Hassan et al, 2018). Elsewhere, disparities in the overall level of participation are attributable to the assertion that CDD varies in terms of objectives, context, country (Mansuri & Rao, 2004) and how participation is measured by researchers (Mbeche et al, 2021).…”
Section: Levels Of Participation In the Cdd Subprojectscontrasting
confidence: 59%
“…The satisfaction with solid waste management services (SWMS) is an effective indicator to evaluate the return or performance of the services provided with consumer satisfaction theories [17][18][19][20][21] and allows a comprehensive evaluation of service efficiency, responsiveness, equity and effectiveness under limited human, material and financial resources [22,23], which can provide feedback and development directions for policy makers and implementers to improve policy and implementation approaches [24]. Some studies of other countries-for example, Malaysia [25], Spain [26,27], Kenya [28], India [29], Slovakia [30] and Italy [31]-also evidenced that satisfaction varies with the situation and quality of SWMS in the areas and countries and demonstrated that 30-84% residents were satisfied with the community SWMS [25][26][27][28][29][30][31][32][33][34][35]. Satisfaction with SWMS will also accelerate residents' separation behavior, services expectations and perceived quality and social interactions among communities [25,26,[36][37][38]; then, it affects community social and environmental sustainability [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The factors that impacted satisfaction when applied to solid waste separation collection, management or treatment services in the previous studies include many items [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Some previous studies have used the structural equation model, service quality (SERVQUAL) model, expectancy disconfirmation model (EDM) or descriptive and factor analysis methods to evaluate the determinants of satisfaction with SWMS or public services [26][27][28][29][30][31][32][33][34][35]39,40,[43][44][45][48][49]…”
Section: Introductionmentioning
confidence: 99%
“…Waste generated disposal knowledge is 2.0% for containers nearby, 22.0% for open spaces, 32.0% for adjacent streams, and 44.0% for regions close to homes. This indicates that there is insufficient understanding and sensitization on the part of the council or service providers on the residents' duty for waste collection, particularly with regard to the ultimate disposal of garbage [26]. Waste collection services have historically been marked by inconsistent collection and insufficient disposal due to the restricted resources available to waste management authorities [11].…”
Section: Summary Of the Various Ways Of Improving The Patronage And O...mentioning
confidence: 99%